A new neotropical species of Monohelea kieffer from Uruguay (Diptera: ceratopogonidae) - Felippe Bauer, Maria Luiza (1998)
A new species of Monohelea Kieffer, M. uruguayensis, is described and illustrated from a male specimen from Uruguay.